Pengaruh Social Proof, Kemudahan, dan Trust terhadap Minat Beli Gen Z di TikTok Shop - Muhammad Sauqi Abdillah; Achmad Syamsul Huda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The study discusses the phenomenon of increasing use of the TikTok application in 2025 and will continue to increase over time and the largest TikTok users in Indonesia among the soaring generation z, this study discusses several factors such as social proof, ease of use and customer trust which are the objects of this study and focus on generation z in the Jabodetabek area. The population and sample are Generation Z in the Jabodetabek area who have shopped at TikTok Shop. And the total respondents obtained were 100 people. The sampling technique used in this study was the non-probability sampling technique using the purposive sampling technique. The data analysis technique used was the Partian Least Square Structural Equation Modeling (PLS-SEM) technique using SmartPLS 4.0 software. The findings in this study are that social proof and ease of use have an effect on the buying interest of generation z in the TikTok shop but are not significant, this finding affects several factors, it could be from the lack of samples used and there are other stronger factors, while customer trust has a positive and significant effect on the buying interest of generation z in the TikTok shop. This study examines how social proof, ease of use and customer trust influence the online buying interest of Generation Z in the Jabodetabek area on the Tiktok Shop platform. From the results of the analysis and findings conducted by the author, the customer trust variable has a positive and significant effect. Social proof and ease of use do not have a significant effect on the online buying interest of Generation Z in the Jabodetabek area on the Tiktok Shop platform.